Reciprocal Interplay Between Astrocytes and CD4+ Cells Affects Blood-Brain Barrier and Neuronal Function in Response to β Amyloid - Spampinato, Simona Federica; Merlo, Sara; Fagone, Evelina; Fruciano, Mary; Sano, Yasuteru; Kanda, Takashi; Sortino, Maria Angela (Frontiers in Molecular Neuroscience, 2020)
Background: In Alzheimer’s disease (AD) neuronal degeneration is associated with gliosis and infiltration of peripheral blood mononuclear cells (PBMCs), which participate to neuroinflammation. Defects at the blood brain barrier (BBB) facilitate PBMCs migration towards the central nervous system (CNS) and in particular CD4+ T cells have been found in areas severely affected in AD. However, the role of T cells, once they migrate into the CNS, is not well defined. CD4+ cells interact with astrocytes able to release several factors and cytokines that can modulate T cell polarization; similarly, astrocytic properties are modulated after interaction with T cells. Methods: in in vitro models, astrocytes were primed with Aβ (2.5 μM, 5 h) and then co-cultured with magnetically isolated CD4+ cells. Cytokines expression was evaluated both in co-cultured CD4+ cells and astrocytes. Effects of this crosstalk were further evaluated by co-culturing CD4+ cells with the neuronal-like SH-SY5Y cell line, and astrocytes with endothelial cells. Results: The pattern of cytokines and trophic factors expressed by CD4+ cells were strongly modulated in the presence of Aβ-primed astrocytes. Specifically, the percentage of IL-4+ and IFNγ+ CD4+cells was significantly increased and reduced, respectively. Further, increased BDNF mRNA levels were observed in CD4+ cells. When SH-SY5Y cells were co-cultured with astrocyte-conditioned CD4+ cells and exposed to Aβ, the reduction of the presynaptic protein, synaptophysin was prevented with a BDNF-dependent mechanism. In astrocytes co-cultured with CD4+ cells, reduced mRNA levels of inflammatory cytokines and VEGF were observed. This was paralleled by prevention of the reduction of claudin-5 when astrocytes were co-cultured with endothelial cells. Conclusion: Following Aβ exposure, there exists a reciprocal crosstalk between infiltrating peripheral cells and astrocytes that in turn affects not only endothelial function and thus BBB properties, but also neuronal behavior. Since astrocytes are the first cells that lymphocytes interact with and are among the principal players in neuroinflammation occurring in AD, understanding this crosstalk may disclose new potential targets of intervention in the treatment of neurodegeneration.